A composite diaphragm and its preparation method and use

By adding lithium titanate -covered ceramic particles to the functional layer of the diaphragm, the existing fast filling membrane is difficult to take into account the problem of fast charging performance and safety performance, and achieves the fast charging performance improvement and thermal stability guarantee of the diaphragm.

CN118073775BActive Publication Date: 2025-01-24REPT BATTERO ENERGY CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410455371.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-16
Publication Date
2025-01-24
Estimated Expiration
2044-04-16

AI Technical Summary

Technical Problem

While improving the lithium ion transmission channel, existing fast charging diaphragms are difficult to take into account both fast charging and safety performance, which easily leads to problems such as lithium dendrites, thermal stability and self-discharge risks.

Method used

By adding lithium titanate-coated ceramic particles into the separator functional layer, the ion diffusion coefficient is increased, the lithium ion transmission path is shortened, and the rate performance and heat resistance of the separator are enhanced.

Benefits of technology

The fast charging performance of the diaphragm is realized, while ensuring the thermal stability of the diaphragm, the amount of lithium titanate is reduced, and the overall performance of the electrolyte infiltration and the overall performance of the diaphragm is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a composite diaphragm and a preparation method and use thereof. The composite diaphragm includes a diaphragm substrate and a functional layer located on at least one side of the diaphragm substrate; the functional layer includes modified particles and a binder, and the modified particles include ceramic particles coated with lithium titanate. In the composite diaphragm provided by the present invention, ceramic particles coated with lithium titanate are added to the functional layer, and the ceramic particles are coated with lithium titanate to realize their surface, improve their ion diffusion coefficient, and reduce the amount of lithium titanate, thereby improving their rate performance and reducing costs; the coated ceramic particles ensure that the diaphragm has good electrolyte wettability, high volume density, and good heat resistance, thereby improving the fast charging performance of the diaphragm while also ensuring the thermal stability of the diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a composite diaphragm and a preparation method and application thereof. Background Art

[0002] With the popularity of electric vehicles, new energy vehicles have limited mileage, and users' demand for fast charging is becoming more and more urgent. Relevant new energy vehicle companies have launched the concept and products of fast charging, that is, charging for 15-30 minutes can achieve about 80% of the designed mileage. The development of fast charging technology is inseparable from the development of battery cell technology. Fast charging of conventional battery cells will lead to problems such as lithium plating in the negative electrode of the battery cell, which will seriously reduce the life of the battery cell. The diaphragm, as a channel for lithium ion transmission inside the battery cell, has an important impact on the development of fast charging technology of the battery cell.

[0003] Traditional fast-charge diaphragms use high-porosity substrates, and high-porosity substrates increase the channels for ion transmission. For example, CN207834428U discloses a high-rate battery diaphragm and a lithium-ion secondary battery. The high-rate battery diaphragm includes a diaphragm body, which has a first face and a second face that are arranged back to back, a plurality of first micropores are distributed on the first face, and a plurality of second micropores are distributed on the second face. The first micropores and the second micropores are connected along a first direction, and the diaphragm body has a plurality of hollow microstructures formed integrally along a second direction. At least one end of the hollow microstructure has an opening connected to the outside, and the first direction and the second direction intersect each other. The substrate has a high porosity in the diaphragm structure provided in the above document. Although it increases the channels for lithium ion transmission to a certain extent, it cannot orderly regulate the deposition of ions, and lithium dendrites are prone to occur at the negative electrode, resulting in safety problems such as thermal stability; it will also reduce the strength of the diaphragm, and the increase in pores also increases the risk of self-discharge, so it is difficult to achieve a diaphragm material that takes into account both fast charging performance and safety performance.

[0004] Therefore, how to improve the fast charging performance of the diaphragm while ensuring the safety performance of the diaphragm is a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a composite diaphragm and its preparation method and use. In the composite diaphragm provided by the present invention, ceramic particles coated with lithium titanate are added to the functional layer, and the ceramic particles are coated with lithium titanate to realize their surface, improve their ion diffusion coefficient, and reduce the amount of lithium titanate, thereby improving their rate performance and reducing costs; the coated ceramic particles ensure that the diaphragm has good electrolyte wettability, high volume density, and good heat resistance, thereby improving the fast charging performance of the diaphragm while ensuring the thermal stability of the diaphragm.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a composite diaphragm, the composite diaphragm comprising a diaphragm substrate and a functional layer located on at least one side of the diaphragm substrate;

[0008] The functional layer comprises modified particles and a binder, wherein the modified particles comprise ceramic particles coated with lithium titanate.

[0009] The composite diaphragm structure provided by the present invention, the addition of modified particles in the functional layer improves the fast charging performance of the diaphragm while ensuring the thermal stability of the diaphragm. Lithium titanate (LTO) is coated on the surface of the ceramic particles and has a high ion diffusion coefficient. The surface treatment thereof also reduces the amount of lithium titanate used, shortens the lithium ion transmission path, and the ion diffusion coefficient, thereby improving the rate performance of the composite diaphragm; it also does not affect the performance of the coated ceramic particles themselves, thereby ensuring that the diaphragm has good electrolyte wettability and good heat resistance.

[0010] In the present invention, lithium titanate must be coated on the surface of ceramic particles to play the role of rapid lithium conduction; if the modified particles in the functional layer are all lithium titanate particles, the manufacturing cost will be greatly increased. At the same time, the volume density of the LTO material is low, and the heat resistance of the diaphragm cannot be effectively improved; if the modified particles in the functional layer are only ceramic particles, the problem of low ion conductivity and poor rate performance cannot be solved; if lithium titanate and ceramic particles are simply physically mixed, that is, they exist in the functional layer in a non-coated form, which increases the cost and is also prone to cause a large difference in lithium ion solubility gradient, affecting the internal uniformity of the battery.

[0011] Preferably, the functional layer is located on both side surfaces of the separator substrate or the functional layer is located on the surface of the separator substrate facing the negative electrode.

[0012] In the present invention, the functional layers are simultaneously arranged on both sides of the separator substrate, which can better improve the heat resistance and lithium ion conductivity of the separator.

[0013] Preferably, the thickness of the functional layer is 1-6 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or 6 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] The thickness of the functional layer provided by the present invention refers to the single layer thickness (i.e., the thickness of the surface of one side of the diaphragm substrate, not the sum of the thickness of the two side surfaces); if the thickness of the functional layer is too thick, exceeding 6μm, it will affect the internal resistance of the battery cell; if the thickness is too thin, less than 1μm, it will be detrimental to the heat resistance of the diaphragm and the wettability of the electrolyte.

[0015] Preferably, the lithium titanate is in-situ coated on the surface of the ceramic particles.

[0016] In the present invention, lithium titanate is in-situ coated on the surface of ceramic particles, which improves the electrical conductivity of the material, improves the fast charging performance of the diaphragm and ensures the thermal stability of the diaphragm.

[0017] Preferably, the D50 of the ceramic particles is 50~2000nm, for example 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm or 2000nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] Preferably, the ceramic particles include any one of aluminum-based ceramic particles, magnesium-based ceramic particles, silicon-based ceramic particles, zirconium-based ceramic particles, titanium-based ceramic particles or barium-based ceramic particles, or a combination of at least two thereof.

[0019] For example, aluminum-based ceramic particles include aluminum oxides (such as aluminum oxide) or aluminum nitrides (such as aluminum nitride), etc.; magnesium-based ceramic particles include magnesium oxides (such as magnesium oxide) or magnesium nitrides (such as magnesium nitride), etc.; silicon-based ceramic particles include silicon oxides (such as silicon dioxide) or silicon nitrides (such as silicon nitride), etc.; zirconium-based ceramic particles include zirconium oxides (such as zirconium oxide) or zirconium nitrides (such as zirconium nitride), etc.; titanium-based ceramic particles include titanium oxides (such as titanium oxide) or titanium nitrides (such as titanium nitride), etc.; barium-based ceramic particles include barium sulfate, etc.

[0020] In the present invention, in addition to the ceramic particles provided above, other types of ceramic particles known to those skilled in the art are also applicable to the present invention.

[0021] It should be noted that the diaphragm substrate provided by the present invention is selected according to conventional technology, and its material, thickness and porosity can be adaptively selected by those skilled in the art.

[0022] Optionally, the diaphragm substrate is selected from any one or a combination of at least two of polypropylene, polyethylene, polymethylpentene, non-woven fabric or polyimide;

[0023] Optionally, the porosity of the diaphragm substrate is 30-70%, such as 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%, etc.;

[0024] Optionally, the thickness of the diaphragm substrate is 5 to 30 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm.

[0025] In a second aspect, the present invention provides a method for preparing the composite diaphragm according to the first aspect, the preparation method comprising the following steps:

[0026] Compounding the functional layer onto the surface of at least one side of the membrane substrate to obtain a composite membrane;

[0027] The functional layer comprises modified particles and a binder, wherein the modified particles comprise ceramic particles coated with lithium titanate.

[0028] The preparation method provided by the invention has a simple preparation process and low cost and is suitable for large-scale production.

[0029] Preferably, the composite method of the functional layer comprises:

[0030] The modified particles, the binder and the first solvent are mixed to obtain a functional layer slurry, and the functional layer slurry is coated on at least one side of the surface of the diaphragm substrate and dried to obtain a composite diaphragm.

[0031] The present invention does not specifically limit the types of the binder and the first solvent. The present invention is applicable to any types of binders and solvents known to those skilled in the art that can be used for preparing the functional layer. The binder includes but is not limited to polyvinylidene fluoride, polyamide, polyvinyl amide or polyimide, etc.; the first solvent includes but is not limited to acetone, N-methylpyrrolidone (NMP) or acetonitrile, etc.

[0032] Preferably, the mass ratio of the modified particles to the binder is (95-5):(5-95), for example, 5:95, 10:90, 15:85, 20:80, 25:75, 30:70, 35:65, 40:60, 45:55, 50:50, 55:45, 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10 or 95:5, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] Preferably, the solid content of the functional layer slurry is 10-90%, for example 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] Preferably, the method for preparing the modified particles comprises:

[0035] Lithium titanate is in-situ coated on the surface of ceramic particles.

[0036] Preferably, the in-situ coating method comprises any one of hydrothermal gel-solid phase sintering, magnetron sputtering or in-situ deposition, or a combination of at least two thereof.

[0037] It should be noted that the present invention is applicable to any method that can realize in-situ coating of lithium titanate on the surface of ceramic particles without affecting the formation of the structure and the performance of the performance.

[0038] Preferably, the method for preparing the modified particles comprises:

[0039] A titanium source, a lithium source, ceramic particles, a second solvent and a complexing agent are mixed to obtain a gel product, which is then sintered to obtain ceramic particles coated with lithium titanate.

[0040] Preferably, the second solvent comprises water and / or ethanol.

[0041] Preferably, the complexing agent is any one of citric acid, oxalic acid or tartaric acid or a combination of at least two thereof;

[0042] Preferably, the titanium source comprises tetrabutyl titanate.

[0043] Preferably, the lithium source includes any one of lithium hydroxide, lithium carbonate or lithium nitrate, or a combination of at least two of them.

[0044] Preferably, the mass ratio of the ceramic particles to the titanium source is (5~100):1, for example 5:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1 or 100:1, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] In the present invention, if the mass ratio of ceramic particles to titanium source is too large, that is, there are too many ceramic particles, it will lead to low ion conductivity and poor fast charging performance; if the mass ratio is too small, that is, there are too few ceramic particles, the heat resistance of the diaphragm will be poor.

[0046] Preferably, the molar ratio of the titanium source to the lithium source is (1-2):1, such as 1:1, 1.5:1 or 2:1, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] Preferably, the mixing method includes stirring, the stirring temperature is 50-80°C, for example, 50°C, 60°C, 70°C or 80°C, and the stirring time is 3-12h, for example, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] Preferably, the gel product is dried and then sintered;

[0049] Preferably, the sintering temperature is 500-1000°C, for example, 500°C, 600°C, 700°C, 800°C, 900°C or 1000°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] Preferably, the sintering time is 3 to 10 hours, for example, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours.

[0051] As a preferred technical solution, the preparation method comprises the following steps:

[0052] Stirring a titanium source, a lithium source, ceramic particles, a second solvent and a complexing agent at 50-80° C. for 3-12 hours, wherein the mass ratio of the ceramic particles to the titanium source is (5-100):1, and the molar ratio of the titanium source to the lithium source is (1-2):1, to obtain a gel product, drying the gel product, and sintering at 500-1000° C. for 3-10 hours to obtain modified particles of ceramic particles in situ coated with lithium titanate;

[0053] Modified particles, a binder and a first solvent are mixed, and the mass ratio of the modified particles to the binder is (95-5): (5-95) to obtain a functional layer slurry. The functional layer slurry is applied to the surface of at least one side of the diaphragm substrate and dried to obtain a composite diaphragm.

[0054] In a third aspect, the present invention further provides a lithium ion battery, wherein the lithium ion battery comprises the composite diaphragm as described in the first aspect.

[0055] Compared with the prior art, the present invention has the following beneficial effects:

[0056] The composite diaphragm structure provided by the present invention, the addition of modified particles in the functional layer improves the fast charging performance of the diaphragm while ensuring the thermal stability of the diaphragm. Lithium titanate (LTO) is coated on the surface of the ceramic particles and has a high ion diffusion coefficient. The surface treatment thereof also reduces the amount of lithium titanate used, shortens the lithium ion transmission path, and the ion diffusion coefficient, thereby improving the rate performance of the composite diaphragm. It also does not affect the performance of the coated ceramic particles themselves, thereby ensuring that the diaphragm has good electrolyte wettability and good heat resistance. DETAILED DESCRIPTION

[0057] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0058] Example 1

[0059] The present embodiment provides a composite diaphragm, which includes a diaphragm substrate (polyethylene, with a porosity of 38% and a thickness of 9 μm) and a functional layer (with a single-side thickness of 3 μm) located on both sides of the diaphragm substrate, wherein the functional layer includes modified particles and a binder (polyvinylidene fluoride), and the modified particles are alumina ceramic particles coated with lithium titanate (the D50 of the ceramic particles is 800 nm).

[0060] The preparation method of the composite diaphragm is as follows:

[0061] (1) Alumina ceramic particles are added to deionized water, and then tetrabutyl titanate is added and mixed evenly, and then LiOH material is added thereto, the molar ratio of tetrabutyl titanate to LiOH material is 1.25:1, and the mass ratio of ceramic particles to tetrabutyl titanate is 50:1, and then citric acid is added (the mass ratio of citric acid added to ceramic powder is 1:20), and the mixture is stirred at 80°C for 6 hours to obtain a gel product, and the gel product is dried at 100°C for 15 hours to obtain a powder, and the powder is sintered at a sintering temperature of 800°C for 5 hours to obtain modified particles;

[0062] (2) Mixing modified particles, polyvinylidene fluoride and acetone, wherein the mass ratio of the modified particles to polyvinylidene fluoride is 90:10, to obtain a functional layer slurry with a solid content of 50%, coating the functional layer slurry on the surfaces of both sides of the diaphragm substrate, and drying to obtain a composite diaphragm.

[0063] Example 2

[0064] The present embodiment provides a composite diaphragm, which includes a diaphragm substrate (polyethylene, with a porosity of 38% and a thickness of 9 μm) and a functional layer (with a single-side thickness of 4 μm) located on both sides of the diaphragm substrate, wherein the functional layer includes modified particles and a binder (polyvinylidene fluoride), and the modified particles are alumina ceramic particles coated with lithium titanate (the D50 of the ceramic particles is 2000 nm).

[0065] The preparation method of the composite diaphragm is as follows:

[0066] (1) Alumina ceramic particles are added to deionized water, and then tetrabutyl titanate is added and mixed evenly, and then LiOH material is added thereto, the molar ratio of tetrabutyl titanate to LiOH material is 2:1, and the mass ratio of ceramic particles to tetrabutyl titanate is 100:1, and then citric acid is added (the amount of ceramic and citric acid added is 1:20), and the mixture is stirred at 60°C for 6 hours to obtain a gel product, and the gel product is dried at 100°C for 15 hours to obtain a powder, and the powder is sintered at a sintering temperature of 1000°C for 3 hours to obtain modified particles;

[0067] (2) Mixing modified particles, polyvinylidene fluoride and acetone, with the mass ratio of modified particles to polyvinylidene fluoride being 80:20, to obtain a functional layer slurry with a solid content of 40%, coating the functional layer slurry on the surfaces of both sides of the diaphragm substrate, and drying to obtain a composite diaphragm.

[0068] Example 3

[0069] The present embodiment provides a composite diaphragm, which includes a diaphragm substrate (polyethylene, with a porosity of 38% and a thickness of 9 μm) and a functional layer (with a single-side thickness of 3 μm) located on both sides of the diaphragm substrate, wherein the functional layer includes modified particles and a binder (polyvinylidene fluoride), and the modified particles are silica ceramic particles coated with lithium titanate (the D50 of the ceramic particles is 500 nm).

[0070] The preparation method of the composite diaphragm is as follows:

[0071] (1) Adding silica ceramic particles to anhydrous ethanol, then adding tetrabutyl titanate and mixing evenly, then adding LiOH material thereto, the molar ratio of tetrabutyl titanate to LiOH material is 1.25:1, the mass ratio of ceramic particles to tetrabutyl titanate is 5:1, then adding tartaric acid (the amount of ceramic to tartaric acid added is 1:20), stirring at 50°C for 3 hours to obtain a gel product, drying the gel product at 100°C for 15 hours to obtain a powder, sintering the powder at a sintering temperature of 500°C for 10 hours to obtain modified particles;

[0072] (2) Mixing modified particles, polyvinylidene fluoride and acetone, wherein the mass ratio of the modified particles to polyvinylidene fluoride is 90:10, to obtain a functional layer slurry with a solid content of 50%, coating the functional layer slurry on the surfaces of both sides of the diaphragm substrate, and drying to obtain a composite diaphragm.

[0073] Example 4

[0074] The difference between this embodiment and embodiment 1 is that in this embodiment, during the in-situ coating process of lithium titanate, the mass ratio of alumina ceramic particles to tetrabutyl titanate is 3:1.

[0075] The rest of the preparation methods and parameters were the same as those in Example 1.

[0076] Example 5

[0077] The difference between this embodiment and embodiment 1 is that in this embodiment, during the in-situ coating process of lithium titanate, the molar ratio of alumina ceramic particles to tetrabutyl titanate is 120:1.

[0078] The rest of the preparation methods and parameters were the same as those in Example 1.

[0079] Example 6

[0080] The difference between this embodiment and embodiment 1 is that in this embodiment, the functional layer is only located on one surface of the separator substrate facing the negative electrode side.

[0081] The rest of the preparation methods and parameters were the same as those in Example 1.

[0082] Comparative Example 1

[0083] The difference between this comparative example and Example 1 is that the functional layer in this comparative example is a lithium titanate functional layer, that is, the modified particles are lithium titanate.

[0084] The preparation method of the composite diaphragm is as follows:

[0085] (1) Anhydrous ethanol and tetrabutyl titanate are mixed evenly, and then LiOH material is added thereto, the molar ratio of tetrabutyl titanate to LiOH material is 1.25:1, and then citric acid is added (the mass ratio of the added amount of citric acid to the ceramic powder is 1:20), and the mixture is stirred at 80°C for 6 hours to obtain a gel product, and the gel product is dried at 100°C for 15 hours to obtain a powder, and the powder is sintered at a sintering temperature of 800°C for 5 hours to obtain lithium titanate;

[0086] (2) Mix lithium titanate, polyvinylidene fluoride and acetone, with the mass ratio of modified particles to polyvinylidene fluoride being 90:10, to obtain a functional layer slurry with a solid content of 50%, apply the functional layer slurry to the surfaces of both sides of the diaphragm substrate, and dry to obtain a composite diaphragm.

[0087] Comparative Example 2

[0088] The difference between this comparative example and Example 1 is that the functional layer in this comparative example is an alumina ceramic particle functional layer, that is, the modified particles are alumina ceramic particles.

[0089] In the preparation method, step (1) is not performed, and step (2) is directly performed using alumina ceramic particles as modified particles.

[0090] The rest of the preparation methods and parameters were the same as those in Example 1.

[0091] Comparative Example 3

[0092] The difference between this comparative example and Example 1 is that the modified particles in this comparative example are a mixed material of lithium titanate and alumina ceramic particles (pure physical mixing).

[0093] The preparation method of the composite diaphragm is as follows:

[0094] (1) Anhydrous ethanol and tetrabutyl titanate are mixed evenly, and then LiOH material is added thereto, the molar ratio of tetrabutyl titanate to LiOH material is 1.25:1, and then citric acid is added (the mass ratio of the added amount of citric acid to the ceramic powder is 1:20), and the mixture is stirred at 80°C for 6 hours to obtain a gel product, and the gel product is dried at 100°C for 15 hours to obtain a powder, and the powder is sintered at a sintering temperature of 800°C for 5 hours to obtain lithium titanate;

[0095] (2) Mix lithium titanate, alumina ceramic particles, a binder and a solvent (the mass ratio of lithium titanate, alumina ceramic particles and the binder is 1:1:0.1) to obtain a functional layer slurry, apply the functional layer slurry to the surfaces of both sides of the diaphragm substrate, and dry to obtain a composite diaphragm.

[0096] The performance tests were performed on the diaphragms provided in Examples 1-6 and Comparative Examples 1-3:

[0097] (1) The ionic conductivity and thermal shrinkage of the separator were tested according to the method of GB / T36363-2018, and the results are recorded in Table 1;

[0098] (2) The diaphragms obtained from the above embodiments and comparative examples were made into lithium iron phosphate soft-pack batteries with a designed capacity of 5Ah. The positive electrode was LFP:PVDF:SP=95.5:2.0:2.5, and the current collector was aluminum foil; the negative electrode was graphite:CMC:SBR=97:1.2:1.8, and the current collector was copper foil. Rate charge and discharge tests (charge and discharge voltage range 2-3.65V) were carried out to test the charge cross-current ratio at 5C current, and the results are recorded in Table 1.

[0099] Table 1

[0100]

[0101] From Table 1, we can get:

[0102] From the data results of Example 1 and Examples 4 and 5, it can be seen that during the in-situ coating process of lithium titanate, if the mass ratio of ceramic particles to titanium source is too small, that is, there are too few ceramic particles, it will affect the heat resistance of the diaphragm; and if the mass ratio is too large, it will be unfavorable for improving the ionic conductivity, the polarization will be larger, and the constant current ratio will be reduced.

[0103] It can be seen from the data results of Example 1 and Example 6 that when the functional layer is located on both sides of the diaphragm substrate at the same time, it can better improve the thermal shrinkage and ionic conductivity.

[0104] It can be seen from the data results of Example 1 and Comparative Examples 1-3 that in the diaphragm structure provided by the present invention, only when a functional layer is provided and the modified particles in the functional layer include ceramic particles coated with lithium titanate, can the ionic conductivity of the diaphragm be improved while taking into account the heat resistance of the diaphragm.

[0105] In summary, the composite diaphragm structure provided by the present invention and the addition of modified particles in the functional layer improve the fast charging performance of the diaphragm while ensuring the thermal stability of the diaphragm. Lithium titanate (LTO) is coated on the surface of the ceramic particles and has a high ion diffusion coefficient. The surface treatment thereof also reduces the amount of lithium titanate used, shortens the lithium ion transmission path, and the ion diffusion coefficient, thereby improving the rate performance of the composite diaphragm. It also does not affect the performance of the coated ceramic particles themselves, thereby ensuring that the diaphragm has good electrolyte wettability and good heat resistance.

[0106] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite diaphragm, characterized in that: The composite diaphragm comprises a diaphragm substrate and a functional layer located on at least one side of the diaphragm substrate; The functional layer includes modified particles and a binder, wherein the modified particles include ceramic particles coated with lithium titanate; the lithium titanate is in-situ coated on the surface of the ceramic particles; The mass ratio of the modified particles to the binder is (95-5): (5-95); The D50 of the ceramic particles is 50-2000 nm; The ceramic particles include any one of aluminum-based ceramic particles, magnesium-based ceramic particles, silicon-based ceramic particles, zirconium-based ceramic particles, titanium-based ceramic particles or barium-based ceramic particles, or a combination of at least two thereof; The preparation method of the modified particles comprises: Mixing a titanium source, a lithium source, ceramic particles, a second solvent and a complexing agent to obtain a gel product, and sintering to obtain ceramic particles coated with lithium titanate; The second solvent includes water and / or ethanol; the complexing agent is any one of citric acid, oxalic acid or tartaric acid or a combination of at least two of them; the titanium source includes tetrabutyl titanate; the lithium source includes any one of lithium hydroxide, lithium carbonate or lithium nitrate or a combination of at least two of them; The mass ratio of the ceramic particles to the titanium source is (5-100):1, and the molar ratio of the titanium source to the lithium source is (1-2):

1.

2. The composite diaphragm according to claim 1, characterized in that: The functional layer is located on both side surfaces of the separator substrate or the functional layer is located on the surface of the separator substrate facing the negative electrode.

3. The composite diaphragm according to claim 1, characterized in that: The thickness of the functional layer is 1-6 μm.

4. A method for preparing a composite diaphragm according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: The functional layer is composited onto at least one side of the surface of the diaphragm substrate to obtain a composite diaphragm.

5. The method for preparing the composite diaphragm according to claim 4, characterized in that: The composite method of the functional layer comprises: The modified particles, the binder and the first solvent are mixed to obtain a functional layer slurry, and the functional layer slurry is coated on at least one side of the surface of the diaphragm substrate and dried to obtain a composite diaphragm; the solid content of the functional layer slurry is 10-90%.

6. The method for preparing a composite diaphragm according to claim 4, characterized in that: The preparation method comprises the following steps: Stirring a titanium source, a lithium source, ceramic particles, a second solvent and a complexing agent at 50-80° C. for 3-12 hours to obtain a gel product, drying the gel product, and sintering at 500-1000° C. for 3-10 hours to obtain modified particles of ceramic particles in situ coated with lithium titanate; Modified particles, a binder and a first solvent are mixed, and the mass ratio of the modified particles to the binder is (95-5): (5-95) to obtain a functional layer slurry. The functional layer slurry is applied to the surface of at least one side of the diaphragm substrate and dried to obtain a composite diaphragm.

7. A lithium ion battery, characterized in that: The lithium-ion battery comprises the composite separator according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • High magnification battery separator and lithium ion secondary cell

    CN207834428U

  • Lithium-titanate-coated modified graphite composite anode material, and preparation method and application thereof

    CN102683705A

  • Composite separator, lithium battery and preparation methods thereof

    CN106876633A

  • Negative electrode for lithium ion secondary battery

    JP2020047387A